Successful Treatment of a Pacemaker Infection with Intraperitoneal Daptomycin. Issue 1 (January 2016) - Taegtmeyer, Anne B.; Kononowa, Nina; Fasel, Dominique; Haschke, Manuel; Burkhalter, Felix
We investigated the pharmacokinetics of intraperitoneal administration of daptomcyin in a peritoneal dialysis (PD) patient treated for a pacemaker infection with Staphylococcus epidermidis. After initial start of intravenous daptomycin at 9 mg/kg body weight every 48 hours, the therapy was switched to intraperitoneal administration of 5.3 mg/kg body weight in 1 L icodextrin 7.5% with a dwell time of 12 hours overnight every 48 hours. Therapeutic drug monitoring (TDM) was performed at 4 hours and 24 hours after dose administration. Due to high peak concentration above target peak concentration, the dose was reduced to a final maintenance dose of 3.2 mg/kg body weight. Data from this single case suggest that serum drug concentration above the minimal inhibitory concentration (MIC) can be easily achieved with intraperitoneal administration of daptomycin every 48 hours even with a lower dose, as recommended for the intravenous administration, but measurement of serum concentration and dose adjustments are mandatory in such cases.